Procedimentos médicos invasivos : diferentes variáveis que podem influir na tomada de decisão - Vieira, Rosmari Wittmann (2018)
Introduction: The population's life expectancy has been increased recently. The social conditions' improvement of the population associated with the development and access to new technologies in the health area were probably the factors that contributed in this process. Since Hippocrates, the fundamental basis of the practice of Medicin is to act in the best interest of the patient. In a fair society, individuals can live with dignity and have their rights respected, as a willingness and autonomy to decide, free of coercion and security, about performing an invasive medical procedure. Objective: to evaluate the decision-making capacity and perceived coercion of hospitalized adult and elderly patients submitted to an invasive medical procedures. Methods: A quantitative cross-sectional study included 300 hospitalized patients older than 18 years old, after having been submitted to an invasive medical procedures. The Psychological-Moral Development Instrument was used to evaluate the decision-making capacity, as well as the Coercion Perception Scale. Data were analyzed using descriptive and inferential statistics. The regulatory requirements of Resolution CNS 466/12 and the other guidelines related to research involving human beings were respected. Results: Only two participants did not have psychological-moral development compatible with the ability to make decisions in their best interests, being one adult and one elderly. Regarding the perception of coercion, the majority of patients (82.7%) presented low perception of coercion. Two comparisons were statistically significant. Adult patients had more years of study than the elderly (P = 0.0001). Likewise, patients submitted to emergency procedures had a perception of coercion statistically superior to those submitted to elective procedures (p <0.0001). In elective procedures, all patients, regardless of gender or age, had a low degree of perceived coercion. Finally, it was possible to verify that the decision involved family members and the team of health professionals, besides the active participation of patients. Conclusion: The results showed that almost all the participants of this research have the capacity to make decisions for their best interest, regardless of age, sex, or years of study. The fact that no significant difference was identified between the age groups demonstrates that the elderly population is able to make decisions about their life and health treatment. The results of perceived coercion demonstrated that most participants felt involved in the decision to perform the procedure. Patients undergoing urgent invasive medical procedures were the only ones to present moderate or high perceived coercion.